Bioinformatic analysis of the potential effects on human health of herbicides for alternative use to glyphosate and atrazine - Lorusso, Tomas; Blaustein, Matías; García Carrillo, Mercedes (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
In Argentina, since the mid-90s, an agricultural model based on genetically modified crops and herbicides such as glyphosate and atrazine has been adopted [1]. The resistance of weeds to these herbicides has led to the use of alternatives such as glufosinate ammonium, alachlor and mesotrione, whose effects on human health are poorly studied [2]. This raises concerns, especially for possible carcinogenic effects, which underlines the need for more research on these alternative herbicides [3]. The objective of this study was to evaluate the potential toxicological effect of these alternative herbicides, identifying the proteins that can interact with them directly or indirectly using the STITCH and STRING platforms [4, 5]. Then, those biological processes potentially affected as a consequence of the interaction of these herbicides with the identified proteins were identified. An enrichment analysis was performed on those overrepresented proteins/genes associated with the category “Biological Process” and “KEGG PATHWAYS” from the Gene Ontology and SHINYGO databases respectively [6]. It was found that, in general, these herbicides could affect both signaling pathways related to cell proliferation, programmed cell death, stress response, as well as the cellular response to xenobiotics, processing, maturation and biogenesis of ribosomal RNA. In addition, possible associated pathologies were found, such as neuro-degeneration, Lupus and cancer. These findings are consistent with previous reports on the toxic effects of these herbicides on human health, giving an account of their potential to produce diseases such as different types of cancer [7, 8, 9]